2010
DOI: 10.3414/me09-02-0052
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of an Automatic Sleep Stage Classification by Means of Multiscorer Hypnogram

Abstract: These findings suggest that machine classification is highly consistent with human sleep staging and that error in the algorithm's assignments is rather a problem of lack of well-defined criteria for human experts to judge certain polysomnogram epochs than an insufficiency of computational procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…On our database, overall 76% AR is achieved for symbolic fusion, which is better in comparison to other decision support algorithms, as reported in [10,18,19]. It proved to be an effective method in comparison to decision tree method, which has AR up to 70% [10].…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…On our database, overall 76% AR is achieved for symbolic fusion, which is better in comparison to other decision support algorithms, as reported in [10,18,19]. It proved to be an effective method in comparison to decision tree method, which has AR up to 70% [10].…”
Section: Resultssupporting
confidence: 61%
“…It proved to be an effective method in comparison to decision tree method, which has AR up to 70% [10]. In [18], authors reported 61% AR by using Linear Discriminant Analysis. In [19], authors reported AR of 55.88%, by using K-Nearest Neighbor method.…”
Section: Resultsmentioning
confidence: 99%
“…The advent of computers in the second half of the twentieth century and the rapid increase in their capabilities led to the realization of numerous studies on methods of automatic analysis of sleep and its stages. The two main aspects of the implemented approaches are [23] : (a) most of the work performed signal characteristic extraction by frequency analysis and frequency over time using discrete wavelet transform (DWT), Huang Hilbert transform (HHT), and fast Fourier transform (FFT) [24][25][26][27] , and (b) different parametric and non-parametric methods have been applied in the classification of sleep events and stages, including random forest classifiers, artificial neural networks (ANN), fuzzy logic, nearest neighbor, linear discriminant analysis (LDA), support vector machines (SVM) and kernel logistic regression (KLR) [28][29][30][31][32][33][34][35][36] .…”
Section: Automatic Sleep Stagingmentioning
confidence: 99%
“…Scoring of S-W epochs into four or five categories has been used by various automated scoring systems (67,83) and in several other laboratories (12,63). Raw hypnograms were smoothed, i.e., every 32-s period was assigned to the dominant S-W stage (26). Analysis of rebound sleep.…”
Section: Treatmentsmentioning
confidence: 99%